The molecular basis of beta-thalassemia intermedia in southern China: genotypic heterogeneity and phenotypic diversity - Sun Manna; Zhou Tianhong; Li Liyan; Cai Ren; Shang Xuan; Zhang Xinhua; Chen Wanqun; Xiong Fu; Xu Xiangmin (BMC, 2010)
Abstract Background The clinical syndrome of thalassemia intermedia (TI) results from the β-globin genotypes in combination with factors to produce fetal haemoglobin (HbF) and/or co-inheritance of α-thalassemia. However, very little is currently known of the molecular basis of Chinese TI patients. Methods We systematically analyzed and characterized β-globin genotypes, α-thalassemia determinants, and known primary genetic modifiers linked to the production of HbF and the aggravation of α/β imbalance in 117 Chinese TI patients. Genotype-phenotype correlations were analyzed based on retrospective clinical observations. Results A total of 117 TI patients were divided into two major groups, namely heterozygous β-thalassemia (n = 20) in which 14 were characterized as having a mild TI with the Hb levels of 68-95 g/L except for five co-inherited αααanti-3.7 triplication and one carried a dominant mutation; and β-thalassemia homozygotes or compound heterozygotes for β-thalassemia and other β-globin defects in which the β+-thalassemia mutation was the most common (49/97), hemoglobin E (HbE) variants was second (27/97), and deletional hereditary persistence of fetal hemoglobin (HPFH) or δβ-thalassemia was third (11/97). Two novel mutations, Term CD+32(A→C) and Cap+39(C→T), have been detected. Conclusions Chinese TI patients showed considerable heterogeneity, both phenotypically and genotypically. The clinical outcomes of our TI patients were mostly explained by the genotypes linked to the β- and α-globin gene cluster. However, for a group of 14 patients (13 β0/βN and 1 β+/βN) with known heterozygous mutations of β-thalassemia and three with homozygous β-thalassemia (β0/β0), the existence of other causative genetic determinants is remaining to be molecularly defined.